Eco-Friendly Reduction of Graphene Oxide by Aqueous Extracts for Photocatalysis Applications - Verástegui Domínguez, Luz Hypatia; Elizondo Villarreal, Nora; Martínez Delgado, Dora Irma; Gracia Pinilla, Miguel Ángel (Molecular Diversity Preservation International, 2022)
In the present work, reduced graphene oxide was obtained by green synthesis, using extracts of Larrea tridentata (gobernadora) and Capsicum Chinense (habanero). Graphene oxide was synthesized by the modified Hummers’ method and subsequently reduced using natural extracts to obtain a stable and environmentally friendly graphene precursor. Consequently, the gobernadora aqueous extract was found to have a better reducing power than the habanero aqueous extract. This opportunity for green synthesis allows the application of RGO in photocatalysis for the degradation of the methylene blue dye. Degradation efficiencies of 60% and 90% were obtained with these materials.